A Single Dose of Intramuscular Sulfadoxine-Pyrimethamine as an Adjunct to Quinine in the Treatment of Severe Malaria: Pharmacokinetics and Efficacy - Newton, C. R. J. C.; Winstanley, P. A.; Watkins, W. M.; Mwangi, I. N.; Waruiru, C. M.; Mberu, E. K.; Warn, P. A.; Nevill, C.G.; Marsh, K. (Oxford University Press)
It has been suggested that sulfadoxine-pyrimethamine (SDPM) may be useful in the treatment of severe malaria since it could enhance the killing of parasites by quinine (QN) and it can be given as a single intramuscular injection. Eighty Kenyan children with severe malaria were allocated at random to receive either intramuscular QN alone (quinine dihydrochloride 20 mg salt/kg as a loading dose, followed by 10 mg salt/kg 12 hourly for a total of 6 doses) or the same QN regimen plus one intramuscular injection of SD/PM (sulfadoxine 25 mg/kg, pyrimetharine 1·25 mg/kg). There was no difference in time to defervescence, aparasitaemia, or 50% reduction in parasitaemia, parasite elimination half-life, or mortality between the 2 groups. In addition, the concentrations of SD and PM were measured in 14 children and of QN in 8 of these children. Concentrations needed to achieve synergy against PM-resistant strains of Plasmodium falciparum were achieved in all of the children with severe malaria within the first hour and maintained for more than 72 h. (SDPM) did not perturb the pharmacokinetics of QN.
Abstract
Keywords: Malaria; Quinine; Kenya; Intramuscular injection; Parasitaemia; Plasmodium falciparum; Pharmacokinetics